Social Impact Assessment Of Road Widen in Project In Mullaithivu - Uthayakumar, S.S.; Suthesini, J. (My University, 2017)
Disaster sociology is the study of the relationship between man, culture and surroundings. It is mainly a trend, related to Society and Environment. Therefore it is an essential need to develop the infrastructure of Mullaithivu district and an important activity in relation to the long term development. For that, Social Impact Assessment and Environmental Impact Assessment are considered as important tasks. I collected the sample of Mullaithivu main road (A35) development programs. Here, main roads are included. They are Mullaithivu- Mulliawallai Road and Mullaithivu – Puthukkudiyiruppu road. There both main and secondary objectives in this study which can be listed as follows. The main objective of this study is to evaluate the social impact assessment and Secondary objective is to understand the positive and negative impacts on social, environmental and economic factor, due to the development of road particularly widening in the mullaithivu District and to suggest some possible alternatives and to understand the challenges due to the widening of the road. This study is done within a short period, and the researchers have used the advanced data collection methods such as questionnaires and participation observation. It is better to follow the alternative methods to reduce the disadvantages of the project. This project is very important and policy makers should think that the project provides advantages rather than disadvantages. Therefore the project has to be welcomed by everyone who tries to develop the country through the development of the Northern Province.
Keywords: Social impact assessment; Environmental impact assessment; Social impacts; Disaster; Road development; Road infrastructure projects; Cost benefit analysis